FAKTOR PREDISPOSING, ENABLING DAN REINFORCING DENGAN PENCEGAHAN DBD DI PUSKESMAS LONDUT KABUPATEN LABUHAN BATU UTARA - SIAGIAN, ALINA HARIYATI (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2021)
One of the efforts in controlling Dengue Hemorrhagic Fever (DHF) is to break the chain of transmission by controlling the vector through the eradication of Dengue Hemorrhagic Fever Mosquito Nest, which is an activity to eradicate eggs, larvae and cocoons of Aedes aegypti infectious dengue disease. This study aims to explain how the Relationship between Predisposing, Enabling and Reinforcing Factors with the Prevention of Dengue Hemorrhagic Fever (DHF) in the Working Area of ​​ Public Health Center of Londut, Labuhan Batu Utara Regency, with the type of survey research with cross-sectional design. The population of this study is the whole Head of the Family as many as 18,898 families. The sampling technique uses random sampling with 100 respondents. Data is collected by questionnaire. Data analysis was performed univariate, bivariate with Chi-square test at 95% confidence level, α = 5% and multivariate with multiple logistic regression. The analysis shows that there is a relationship between education (p = 0.032 <p = 0.05), occupation (p = 0.005 <p = 0.05), knowledge (p = 0.006 <p = 0.05), availability of facilities / infrastructure (p = 0.010 <p = 0.05), the role of health workers (p = 0.002 <p = 0.05) with the prevention of Dengue Hemorrhagic Fever (DHF). The most related variable is knowledge OR = 2,968. The management of Public Health Centre of Londut is expected to improve services in the Dengue Hemorrhagic Fever program to prevent an increase in dengue cases in the working area of ​​Public Health Centre of Londut.